2014
DOI: 10.3109/02699052.2014.887228
|View full text |Cite
|
Sign up to set email alerts
|

Delayed gait disturbance due to injury of the corticoreticular pathway in a patient with mild traumatic brain injury

Abstract: It appears that the proximal weakness of this patient was attributed to injury of both CRPs following head trauma. It is assumed that the mild weakness at the onset of head trauma was caused by the primary traumatic axonal injury and the aggravated weakness that started from 29 days might be ascribed to the secondary traumatic axonal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…In this case report, by using DTT, we were able to detect injuries of the STT, CST, CRT, and fornix in a patient with whiplash injury, and the neural injuries were consistent with the clinical features of this patient; that is, central pain (injury of the STT), quadriparesis (injury of the CST and CRT), and memory impairment (injury of the fornix) [10][11][12][13][14][15][16][17][18]. Because no definite brain lesion was observed on conventional brain MRI, TAI appeared to be the most likely pathogenetic mechanism for injuries of these neural tracts [18,23].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In this case report, by using DTT, we were able to detect injuries of the STT, CST, CRT, and fornix in a patient with whiplash injury, and the neural injuries were consistent with the clinical features of this patient; that is, central pain (injury of the STT), quadriparesis (injury of the CST and CRT), and memory impairment (injury of the fornix) [10][11][12][13][14][15][16][17][18]. Because no definite brain lesion was observed on conventional brain MRI, TAI appeared to be the most likely pathogenetic mechanism for injuries of these neural tracts [18,23].…”
Section: Discussionsupporting
confidence: 56%
“…Recently, with the introduction of diffusion tensor imaging (DTI), several studies have used diffusion tensor tractography (DTT), which is derived from DTI data, to demonstrate traumatic axonal injury (TAI). In patients with whiplash injury, TAI is the tearing of axons, due to indirect shearing forces during acceleration, deceleration, and rotation of the brain [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…10Y12 In 2013, Yeo et al 10 reported on discontinuation of the CRP at the midbrain level in a patient with a contusional hemorrhage in the right frontotemporal lobes who showed proximal weakness. In 2014, Kwon and Jang 11 reported on a patient who showed gait disturbance and quadriparesis with more severe weakness of the proximal joints due to injury of both CRPs following mild TBI. Lee et al (2015) recently demonstrated injury of the CRP in 29 patients with proximal weakness after mild TBI.…”
Section: Discussionmentioning
confidence: 99%
“…After the introduction of diffusion tensor imaging (DTI), many studies using diffusion tensor tractography (DTT), which is reconstructed from DTI data, have demonstrated neural injuries of various neural tracts in patients with cerebral concussion or mild traumatic brain injury (TBI) who showed no abnormal lesion on conventional brain MRI [11][12][13][14][15]. Among these studies, several studies have reported injury of neural tracts and their relavant clinical symptoms following whiplash injury [16][17][18][19]. These neural tracts comprise the corticospinal tract, the corticoreticulospinal tract, the dentatorubrothalamic tract, the ascending reticular activating system, and the spinothalamic tract [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Among these studies, several studies have reported injury of neural tracts and their relavant clinical symptoms following whiplash injury [16][17][18][19]. These neural tracts comprise the corticospinal tract, the corticoreticulospinal tract, the dentatorubrothalamic tract, the ascending reticular activating system, and the spinothalamic tract [16][17][18][19]. Regarding auditory radiation, although a case study has been reported, which demonstrated the relation between sensorineural hearing loss and auditory radiation injury, no study on tinnitus related to auditory radiation injury has been reported [20].…”
Section: Introductionmentioning
confidence: 99%